Oil distribution and oil film thickness within the piston ring-liner contact measured by laser-induced fluorescence in a reciprocating model test under starved lubrication conditions. (January 2019) - Obert, Petra; Füßer, Hans-Jürgen; Bartel, Dirk
Abstract: For a better understanding of the most important parameters and boundary conditions for scuffing initiation in the piston ring versus cylinder liner contact at fired top dead center of internal combustion engines, oil distribution measurements were performed by means of laser-induced fluorescence (LIF) on a reciprocating test rig. The 2D LIF measurements showed the change of the oil distribution in and around the contact area and verified that the oil available in the contact during the test decreased gradually over time until scuffing was initiated. For an improved quantification and increased detection limit of the oil film thickness within the contact, a sheet-of-light method was implemented, which enables evaluation of oil film thicknesses below 0.05 μm and by which it was possible to study oil film thicknesses in the range of the surface roughness level of the counterparts. The decrease of the oil supply at the leading edge of the contact area just before scuffing initiation and the corresponding very low oil film thickness below the roughness level of the surfaces was quantitatively evaluated and proved that oil starvation was an important parameter for scuffing between piston ring and cylinder liner. Highlights: Application of laser induced fluorescent (LIF) technique on SRV. 2D-LIF measurement showed change of the oil distribution of the contact area. Sheet of light method for quantitative oil film thickness measurement implemented. Oil film thickness below 0, 05 μm in the tribological contact were measured. Oil starvation as important parameter for scuffing proved.